PERCEPTIONS OF ELT STUDENTS ON THEIR LISTENING AND NOTE TAKING SKILLS - Hülya İpek (Informascope, 2018)
Notetaking is regarded as an academic skill necessary to pursue ones academic studies. Note taking while listening to lectures is a challenging activity for non-native speakers studying in a foreign language. It is advised that non-native students should be trained in listening and note taking which will help them to improve their listening comprehension and notetaking skills. Also, it is indicated that students express a positive opinion about such training (Flowerdew & Miller, 1992; Hayati & Jalilifar, 2009; Crawford, 2015). This study aimed to investigate first year English Language Teaching (ELT) students' perceptions on their progress in listening and notetaking. It was conducted with 61 Freshman ELT students. Data were collected through a questionnaire comprised a 3 point Likert scale with 8 items including aspects such as using abbreviations and symbols, noting down only important information, and organizing main ideas and details. 1 open ended question was also used in the questionnaire to support the quantitative data. According to the results, students expressed the most progress in writing down important words, separating and recognizing main ideas, and using abbreviations and symbols.